Sosialisasi Pengetahuan Mengenai Kesehatan Reproduksi Seksual Bagi Remaja Di Desa Kungkai Baru, Kecamatan Air Periukan, Kabupaten Seluma, Bengkulu - Himawati, Ika Pasca; Nopianti, Heni; Hartati, Sri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Problem about free sex, HIV/AIDS and sexual transmitted infection is due to minimum knowledge in adolescent about sexual reproduction health. In fact, knowledge about sexual reproduction is an important factor in attempt to make physical and mental health of adolescent. For that reason, socialization about sexual reproduction for adolescent is necessary. This activity was intended for adolescent in Kungkai Baru village, Air periukan sub district, Seluma Region. In addition, this activity was conducted as an attempt to support the existing Posyandu Remaja (adolescent health service center). The final purpose of this activity is that to give openness of knowledge and horizon about the importance of sexual reproduction health for adolescent in Kungkai Baru village, Air periukan sub district, Seluma Region, Bengkulu.